2002
DOI: 10.1046/j.1365-2303.2002.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Warthin's tumour: unusual vs. common morphological findings in fine needle aspiration biopsies

Abstract: Fine needle aspiration biopsies (FNA) of 47 Warthin's tumours confirmed by histology were re-evaluated for cytomorphological findings. The majority of aspirates (37/47) contained a typical background with proteinaceous substance and cell debris, along with cellular elements represented by oncocytic, lymphoid, and mast cells with degranulated cytoplasm. Uncommon cellular findings were true squamous cells (1/47), atypical cells with vacuoles (1/47), osteoclastic giant cells (1/47), epithelioid cells (1/47), mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 12 publications
8
45
0
Order By: Relevance
“…The cytological accuracy was 81% (3 cases had a preoperative FNA suggesting a malignant tumor) [5]. In another study, 37 out of 47 patients (79%) had a correct FNA diagnosis confirmed by histology [6]. Similar to these results, the sensitivity in our series was 78.7%.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The cytological accuracy was 81% (3 cases had a preoperative FNA suggesting a malignant tumor) [5]. In another study, 37 out of 47 patients (79%) had a correct FNA diagnosis confirmed by histology [6]. Similar to these results, the sensitivity in our series was 78.7%.…”
Section: Discussionsupporting
confidence: 86%
“…It typically presents as a slow-growing parotid mass. Squamous metaplastic cells may be identified in more than 60% of cases [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a growing body of evidence suggest that this examination does not provide adequate diagnostic accuracy, especially in the case of small and/or deeply located lesions. In up to 5% of the cases, material obtained during biopsy of such tumours may be not representative enough to determine their character [6,14,16,23]. Moreover, an incorrectly performed biopsy may lead to various complications, including systemic spread of cancer cells and ascending infection of the head and neck [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a background rich with lymphocytes and granular debris, the recognition of oncocytic cells make the diagnosis straightforward and accurate, in most cases. On occasion, however, unusual features challenge even the experienced cytopathologist [1,2]. In particular, squamous or mucinous metaplasia changes may overlap with mucoepidermoid carcinoma features [1,2,3].…”
Section: Introductionmentioning
confidence: 99%